2021
DOI: 10.3892/etm.2021.10193
|View full text |Cite
|
Sign up to set email alerts
|

circSKIL promotes the ossification of cervical posterior longitudinal ligament by activating the JNK/STAT3 pathway

Abstract: Ossification of the posterior longitudinal ligament (OPLL) is a hyperostotic spinal condition that involves genetic factors as well as non-genetic factors, and its underlying molecular mechanism is largely unknown. Recently, circular RNAs (circRNAs) have been attracting the attention of researchers since they have important regulatory roles in many diseases, including bone metabolism disorders. The present study aimed to investigate the role of circRNA SKI-like proto-oncogene (circSKIL) in OPLL disease progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The activation of JNK/STAT3 signaling promoted the inflammation, which was confirmed to regulate the M1 polarization of BV2 cells (Sun et al., 2021 ; Wan & Sun, 2019 ). In addition, our finding found the upregulation of PPAR‐γ was able to inhibit this signaling, which confirmed Rosiglitazone could inhibit microglia M1 polarization through inactivating JNK/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 87%
“…The activation of JNK/STAT3 signaling promoted the inflammation, which was confirmed to regulate the M1 polarization of BV2 cells (Sun et al., 2021 ; Wan & Sun, 2019 ). In addition, our finding found the upregulation of PPAR‐γ was able to inhibit this signaling, which confirmed Rosiglitazone could inhibit microglia M1 polarization through inactivating JNK/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 87%
“…circCDR1‐AS, by sponging miR‐7, up‐regulated growth differentiation factor 5, which promoted osteoblastic differentiation of PDLCs via activating both Smad and p38 signaling 20 . Sun et al identified the up‐regulation of circSKIL in posterior longitudinal ligament cells from patients suffering from cervical spondylotic myelopathy with ossification of cervical posterior longitudinal ligament (OPLL) and revealed that the ossification‐promoting impacts of circSKIL was mediated through the activation of JNK/STAT3 pathway 21 . Here, we demonstrated the essential and sufficient effects of circSKIL in stimulating the osteoblastic differentiation of PDLCs.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA expression profiles in primary posterior longitudinal ligament cells Sun et al (2021) found that circSKIL expression levels were significantly elevated in primary cervical posterior longitudinal ligament cells from patients with OPLL and promoted osteogenic differentiation through the JNK/STAT3 pathway. In addition, the overexpression of circSIKL can also improve the expression levels of RUNX2, ALP, COL I, OCN and OPN, thus proving the role of circSIKL in the ossification of the posterior longitudinal ligament.…”
Section: Circrna Expression Profiles In Ossification Of the Posterior...mentioning
confidence: 99%